Strategi Pengembangan Usaha Suwar Suwir “Abi” di Desa Panti Kecamatan Panti Kabupaten Jember (Studi kasus : Di Desa Panti Kecmatan Panti Kabupaten Jember) - Nisa, Khoirun; Pudjiastutik, Endang Wahyu (KUBIS, 2021)
ABSTRACT Indonesia is an agricultural country that has abundant natural resources in the form of agricultural products. The food crops sub-sector is one of the agricultural products that has an important role as a supplier of consumption needs. The aims of the research were (1) to know the 4p marketing mix/marketing mix of the “abi” suwar suwir business in Panti Village, Panti District, Jember Regency. (2) To find out the development strategy in the "abi" suwar suwir business in Panti Village, Panti District, Jember Regency. The research method is using Qualitative Descriptive Analysis, and data analysis by observation, interviews and questionnaires. The results of this study indicate that those using the marketing mix4p analysis of the "Abi" suwar suwir business have not fully implemented the marketing mix4p properly. Among other things, in terms of packaging, promotion, and the lack of human resources. The results of the SWOT analysis show that the position of the SWOT matrix diagram is in a positive aggressive strategy, positive in square 1 is obtained from reducing the number of strengths, weaknesses and opportunities and threats, this is a favorable situation. The marketing strategy has opportunities and strengths. Keywords : Suwar Suwir, Marketing mix4p, SWOT